Pembelajaran analisis zat gizi dengan model learning cycle 5-E - Inma Yunita Setyorini (University of Darussalam Gontor, 2017)
The implementation of the learning process has an important influence for the successful of the university student’s learning. The less appropriate learning process will make the university studets are not focus and less interested in following the learning activity. Therefore, it needs an appropriate learning model to learn which can emphasize that the learning model can give a direct experience to the university students. One of the learning model which constructivist based, such as Learning Cycle 5-E learning model. The purpose of this study is to know the difference of the learning outcome between the class who are given by Learning Cycle 5-E learning model with the students who are given by expository learning model in the cognitive and affective aspect.The design used in this research is descriptive quantitative that is a research design of quasi experimental. The technique of sampling used in this research is purposive sampling with total research subjects are 61 university students.The technique of data analysis used in this research are descriptive and statistic analysis. Descriptive analysis used to reveal the learning outcome of the affective aspect. Statistic analysis used to examine cognitive learning outcome uses the t-test. The average of affective learning outcome of the students who are given by Learning Cycle 5-E learning model is higher then the average of affective learning outcome of the students who are given by expository learning model . The average of cognitive learning outcome of the university students who are given by Learning Cycle 5-E learning model ( is higher than the average of cognitive learning outcome of the students who are given by expository learning model .